Integration of Miniaturized Array Antenna With High-Permittivity Rectangular Bismuth Titanate for WiMAX Applications - Al-Amani, Umar (2012)
High-permittivity rectangular bismuth titanate (ReBiT) array antennas for WiMAX application have been investigated, fabricated, and measured. The antennas are designed and constructed with a combination of two-, four-, and six-BiT elements in an array form stacked on a microwave substrate. The impedance bandwidth of the ReBiT is 350 MHz, and it is able to operate in the frequency range of 2.20 to 2.55 GHz, which is suitable for the application of aWiMAX 2.30 GHz system. The utilization of a bismuth titanate (BiT) ceramic that covers about 90% of the antenna led to high radiation efficiency, low cost, and the production of small-size antennas.